The association between white blood cell counts and metabolic health obesity among US adults - Li, Zhanbin; Yao, Zhenyu; Liu, Qiaoran (Frontiers in Nutrition, 2025)
BackgroundThe correlation between white cell count and metabolically healthy obesity (MHO) remains elusive among obese American adults. This study endeavors to elucidate this association.MethodsThis study enrolled 6,580 obese patients from the National Health and Nutrition Examination Survey (NHANES). Obesity phenotypes were defined by presence/absence of metabolic syndrome components. Weighted multivariate logistic regression analyses were used to assess the association between white cell count and MHO occurrence. Restricted cubic spline analysis characterized dose–response relationships, and stratified analyses explored these relationships across sociodemographic and lifestyle factors.ResultsIn this study, MHO prevalence is 11.9% among obese adults. The risk of MHO was inversely correlated with WBC [OR (95%): 0.81 (0.76, 0.86), p < 0.001], lymphocytes [OR (95%): 0.56 (0.47, 0.68), p < 0.001], monocytes [OR (95%): 0.41 (0.22, 0.75), p = 0.004], and neutrophils count [OR (95%): 0.82 (0.76, 0.88), p < 0.001]. WBC and neutrophils showed L-shaped associations, while lymphocytes, monocytes, and RBCs had linear patterns. Furthermore, stratified analyses demonstrated blood cell counts consistently predicted MHO risk across subgroups.ConclusionIn this study, we provide novel insights into the association between blood cell count and the presence of MHO among obese individuals. Blood cell count is an accessible biomarker for dynamically tracking the presence of MHO.